Nutrition Services Strategy in Toddlers - Piuskosmas Fau; Otniel Kataren; Mestika Lumbantoruan (Science Midwifery, 2022)
The World Health Organization (WHO) states that infant mortality is caused by nutritional problems. The study used a qualitative method with a phenomenological approach to nutrition service strategies for toddlers. The research informants are the Head of the Puskesmas, the person in charge of the nutrition program, the village midwife, the staff of the public health sector of South Nias Regency. The research was conducted in November 2018-July 2019. Internal factors of the Bawomataluo Health Center in nutritional services for toddlers are the availability of health services, the budget for nutrition services, SOPs for nutrition services, health efforts through the availability of nutrition counseling rooms, lack of human resources, the nutritional status reporting system which is still manual. External factors: work partners, support from the government, community creativity in managing food, low economy, damaged infrastructure, behavior and culture of the community who are less concerned with the nutritional needs of toddlers. Alternative strategies that can be used for nutritional services to children under five at the puskesmas are by utilizing the budget with partners, improving nutrition service facilities, providing additional food, increasing training, providing demonstrations of good food ingredient management, increasing human resources, improving technology-based reporting systems.